Effect of Thickness of Nanofiber Separator Membrane PAN/PVDF on Supercapacitor’s Performance - Agustina, Silvia Nurlaili; Diantoro, Markus; Hartatiek, Hartatiek; Nasikhudin, Nasikhudin (Journal of Mechanical Engineering Science and Technology (JMEST), 2025)
Separators in supercapacitors have an important role as intermediaries for ions that pass during the charge-discharge process and affect the performance of supercapacitors. Therefore, a comprehensive study is needed related to separator characteristics, including morphology, pore size, diameter, functional group, and electrochemical performance of separator membranes from PAN/PVDF composites. The separator membrane was synthesized using the electrospinning method with thickness variation (2, 4, 6, 8, and 10 layers), followed by supercapacitor fabrication with coin cell device. The resulting membrane was then characterized by Scanning Electron Microscope (SEM) and Fourier Transform Infrared (FTIR). For the result of supercapacitor fabrication with coin cells, Galvanostatic Charge-Discharge (GCD), Cyclic Voltammetry (CV), and Electrochemical Impedance Spectroscopy (EIS) were carried out to determine supercapacitor performance. FTIR results showed that the PAN/PVDF membrane was successfully composites with the addition of new peaks identified as PVDF and PAN at wave numbers 2243.21 and 881 cm-1. The nanofibers formed have diameters ranging from 319.7 to 339.95 nm. The optimum percentage of electrolyte uptake is obtained at membranes that have 6 layers, which is 318.18% and decreases to 173.68% the thickness is 10 layers. In this study, the optimum supercapacitor performance was obtained in the 6 layers variation with a thickness of 75.91 x 103 nm with a gravimetric capacitance value is 53.36 F/g, the capacity retention is 88.96% after being tested for 500 cycles, the largest curve area of CV, and an ionic conductivity value is 54 x 10-5 S/cm.